2013
DOI: 10.1111/are.12140
|View full text |Cite
|
Sign up to set email alerts
|

Blue mussel meal as feed attractant in rapeseed protein-based diets for turbot (Psetta maximaL.)

Abstract: Antinutritional factors in rapeseed products have been identified to reduce feed palatability and growth performance of turbot. Therefore, we evaluated the potential of blue mussel (Mytilus edulis L.) meal as feed attractant in rapeseed protein-based diets for turbot. Triplicate fish groups received isonitrogenous and isocaloric diets with fish meal (FM) protein replacements of 50% or 75% by rapeseed protein concentrate (RPC 50, RPC 75). These diets were supplemented with 0%, 2%, 4% or 8% of blue mussel meal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 67 publications
(111 reference statements)
3
49
1
1
Order By: Relevance
“…The HSI (1.41 and 1.45) is in the normal range for turbot (Fournier et al., ; Nagel et al., , ; Peres & Oliva‐Teles, ), indicating a good status of energy reserves and no impairment of the health status. The SGR in experiment A is comparable to the SGR in other studies with turbot of the same size (Fuchs et al., ) and seems to be quite good in the 0% diet, which proves the good quality of our test diet.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The HSI (1.41 and 1.45) is in the normal range for turbot (Fournier et al., ; Nagel et al., , ; Peres & Oliva‐Teles, ), indicating a good status of energy reserves and no impairment of the health status. The SGR in experiment A is comparable to the SGR in other studies with turbot of the same size (Fuchs et al., ) and seems to be quite good in the 0% diet, which proves the good quality of our test diet.…”
Section: Discussionmentioning
confidence: 98%
“…Our results indicate that replacement of 10%–25% fishmeal with mussel meal can be recommended in feed for turbot raised in aquaculture. Previous studies already recommended mussel meal as a feed attractant in lower concentrations (Kikuchi et al., ; Nagel et al., ) to disguise an unfavourable taste in plant‐derived alternative protein sources and to encourage feed uptake. A feed formulation combining non‐fish marine protein sources and plant‐derived proteins should be in the focus of future feed stuff research.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of several other studies on turbot. Here, growth performance and feed conversion were negatively affected by the administration of various plant proteins in general (Fournier, Huelvan, & Desbruyeres, ; Nagel et al, ) or SBM and mixtures of both in particular (Bai et al, ; Bonaldo et al, , ; Gu et al, ; Sevgili et al, ; Yun, Mai, Zhang, & Xu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we could not detect an obvious aversion against any of the diets offered. The proper palatability was possibly achieved by supplementing our experimental diets with an attracting mussel meal (Nagel et al, ). Only in the SBM + degrad treatment we recognized that fish occasionally disgorged a few feed pellets.…”
Section: Discussionmentioning
confidence: 99%
“…Nagel et al . () demonstrated that the utilization of mussel meal improved the palatability of rapeseed protein‐based diets for turbot, and Mazzoni et al . () used mussel meal as gustatory stimulants to improve the palatability of commercial diet for sole.…”
Section: Mussels As a Sustainable Alternative For Fishmeal Replacemenmentioning
confidence: 99%